PENERAPAN METODE PEMBERIAN TUGAS DALAM MENINGKATKAN KEMAMPUAN MENULIS SURAT PRIBADI PADA SISWA KELAS VII.3 DI SMP NEGERI I TAMBANG KABUPATEN KAMPAR - Zulkifli, Zulkifli (EDUTECH CONSULTANT, 2017)
This research is motivated by the lack of ability to write a personal letter class VII SMP Negeri 1 Mine Kampar. This study aims to improve the ability to write a personal letter VII.3 grade students in Junior High School I Mines Kampar above will be discussed with the method of assignment, which is carried out for 1 month. The subjects were VII.3 grade students in Junior High School I Mines Kampar, amounting to 22 people consisting of 11 men and 11 women. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity, average students on the initial tests are categorized either by the average value of 62.5 and the the first cycle rose to 67.0 in both categories, while in the second cycle of average ability students have been categorized as good with an average value of 81.0, but with completeness 100%, where the value of mastery students have tercapi. The above statement shows that the ability to write a personal letter VII.3 grade students in Junior High School I Kampar Regency Mines can be improved through the method of administration tasks. Thus the research hypothesis that read Personal Letter Writing ability can be improved by Giving Methods Task Against VII.3 Grade Students in Junior High School I Mines Kampar